Effect of charging protocols on electrochemical performance and failure mechanism of commercial level Ni-rich NMC811 thick electrode - Nutthaphon Phattharasupakun; Panyawee Bunyanidhi; Poramane Chiochan; Narong Chanlek; Montree Sawangphruk (Electrochemistry Communications, 2022)
In order to bridge the gap between academia and industry in the development of cathode active material for high-energy lithium-ion batteries (LIBs), several experimental factors reflecting commercial use need to be considered. Herein, based on a thick commercial level NMC811 electrode, we simply demonstrated the effect of charging protocols on the rate performance, cycling stability, and Li storage mechanism. A constant current charge/discharge, typically used in most publications, was found to exhibit worse rate capability and cycling stability compared to the constant current constant voltage (CCCV) mode of charge, used in commercial LIB cells due to the less uniform Li concentration gradient between the surface and bulk of the material. In operando XRD also revealed that there was no negative impact from the rapid change in lattice parameters towards cycling performance. We also found that the major degradation mechanism of Ni-rich NMC811 showing poor cycling performance across literature, can be mainly ascribed to the thick cathode electrolyte interphase (CEI) resistive layer, hindering Li intercalation at high rate and also lead to lower accessible capacity in each cycle. This work illustrates a simple example of the gaps between research in academic and industry that need to be narrowed for the development of practical high energy materials.